Virtual Dialogue in Ayu's Novel - Ghazi Al-Yasri, Assist.Prof.Dr. Ashwaq (Basra studies journal, 2026)
This study is an attempt to understand the effect of digital worlds and artificial intelligence applications in literature. Since their introduction in the last two decades , literary research has witnessed a promising transformation in its scientific and cognitive journey. The novel, as the most distinctive text in this type of application, demonstrates this ability to interact consciously and cautiously at the same time. What we are trying to study here relates to writers' use of this technology and its introduction into the world of creative writing, where it is used as a character in "electronic chat", which demonstrates its effectiveness in generating new ideas related to the possibility of creating expressive spaces worthy of affirming the new relationship between humans and machines. By employing dialogue technology as a tool for narrative overlap and a plot driver in an era witnessing the increasing presence of machines. In addition the study is studying the narrative charter in the dialogue transforms from character interrogation to a narrative text parallel to the novel. This is a clear indication of the transformation in the relationship between humans and machines, raising many questions about the usefulness of communication in a virtual world and the degree of awareness that contemporary humans have reached in the digital age. It also reveals identity and its impact on dialogical existence.